Exploring the effects of community immersion on the interpersonal skills of Davao Medical School Foundation clerks with patients during medical interviews 2003-2004 clerkship program - Hontiveros, Erwin Rommel N.; Nemuel S. Fajutagana, MD, MHPED (2005)
Davao Medical School Foundation (DMSF) was established in 1976 to respond to the health needs of the rural as well as the urban underserved communities of Mindanao. This is achieved by training students to become competent general practitioners. During clerkship, the students' daily activities include interviewing and examining patients, attending ward rounds, and performing basic clinical procedures. Despite the inclusion of patient-care attitudes in student evaluation, good interpersonal behaviors by clerks toward patients were not uniformly observed. On one side of the continuum, isolated cases of inappropriate behaviors allegedly done by some DMSF clerks to patients while assigned in teaching hospitals were observed. On the other side of the continuum, appropriate interpersonal behaviors by clerks toward patients while assigned in rural communities were noted. This study explored the effects of community immersion on the interpersonal skills of DMSF clerks with patients during medical interviews. The interpersonal skills of fifty-eight fourth year clerks, batch 2004 of DMSF during medical interviews with patients were compared in terms of hospital assignment, service department rotation and community immersion experience. Furthermore, the interpersonal skills of fourteen clerks of the same batch were compared as they go through three rotations (pre-community immersion, during community immersion and post-community immersion). Two separate checklists for interpersonal skills developed by Mencias (1991) were used by trained observers and randomly selected patients. In the analysis of their mean performance, clerks rotated in private hospitals performed better on interpersonal skills as compared to clerks rotated in the public hospital (p=0.000<0.05). In terms of service department rotation, there was no significant difference in performance on interpersonal skills among clerks rotated in Internal Medicine, Obstetric-Gynecology, Pediatrics and EENT-Dermatology (p=0.105>0.05). In like manner, there was no significant difference in performance on interpersonal skills among clerks who have undergone community immersion and those who were yet to undergo community immersion (p=0.563>0.95). When the interpersonal skills of fourteen clerks were compared through three phases of their clerkship training, their performance on interpersonal skills improved during community immersion and post-community immersion as compared to their pre-community immersion rotation. When rotated to hospitals, survey results cited frequent history taking, explaining clinical procedures and doing progress notes as experiences that enhanced clerks' IPS while lack of rest, excessive workload, absence of role models and less trust accorded by patients frustrated clerks' skills on interpersonal relationships. In the community, routine history taking, lecturing health programs, doing community diagnosis, experiencing community life, and the absence of clinical preceptors enhanced clerks' IPS, while lack of interest by rural residents in the absence of free medicines, limited stay in the community and difficulty adjusting to community life frustrated clerks' skills on interpersonal relationships. This study recommends the following measures to the Curriculum Committee of DMSF, a) to include patients in medical student's interview assessment, thereby providing students with relevant and specific interview skills feedback and learner support; b) provide clinical preceptors with constant student feedback to increase their awareness of their role in the development of student's competency in interpersonal relationships with patients and other health care providers; c) provide more clerk-patient contact at the community level, to enable clerks more contact time to the majority of the people and with it, gain more insights to socio-economic factors that contributed to the health condition of the patient; and d) further study on why empathy gradually declined while acceptance gradually improved during and after community immersion.
Thesis (Master in Health Professions Education)--University of the Philippines Manila
Panel Members: Nemuel S. Fajutagana MD MHPEd, Chair/Adviser; Cristina F. Mencias MHPEd PhD, Reader/Critic; Jose Alvin P. Mojica MD MHPEd, Member; Erlyn A. Sana PhD, Member; Lupe F. Abarquez BSN MHPEd, Member; Delen Dela Paz MD, Member.
Keywords: Clinical clerkship; Community immersion